Efficient dye-sensitized solar cells with broad absorption and enhanced photo-current generation. Issue 62 (14th June 2016) - Kim, Jihun; Lee, Horim; Kim, Dong Young; Seo, Yongsok
Abstract : Metal-free organic dyes comprising donor, electron-conducting, and acceptor moieties with anchoring groups were synthesized for the sensitization of hierarchically structured TiO2 (HS-TiO2 ) nanoaggregates of TiO2 electrode. Abstract : Metal-free organic dyes comprising donor, electron-conducting, and acceptor moieties with anchoring groups were designed and synthesized for the sensitization of hierarchically structured TiO2 (HS-TiO2 ) nanoaggregates of TiO2 electrode. The performance of JH-2 in a dye sensitized solar cell (DSSC) was compared with the performances of JH-1 and PTD-02. The DSSC of JH-2 with the HS-TiO2 electrode yielded an unprecedented high photocurrent density of 21.62 mA cm −2, an open circuit voltage of 691 mV and a fill factor of 0.631, and an overall efficiency of 9.42% under standard AM 1.5 sunlight. These were superior to those obtained from the JH-1 DSSC or the PTD-02 sensitizer, which has a chemical structure similar to JH-1, but displayed a much lower photocurrent density and efficiency. The performance of JH-2 DSSC developed here can offer an efficiency comparable to that of a popular ruthenium-coordinated dye (N719) while providing better long-term stability even without a UV filter.